Framing the mass shooter James Eagan Holmes: serious mental illness and gun violence - Martinez, Nikki Lee, author; Humphrey, Michael, advisor; Christen, Cindy, committee member; Rosen, Lee, committee member (Colorado State University. Libraries, 2019)
This study examined the framing of serious mental illness (SMI) and gun violence focused on the single case of the 2012 Aurora Theater Shooting perpetrated by James Eagan Holmes. At the time, it was the most devastating mass shooting in U.S. history with 58 injured and 12 killed. The overarching question guiding the study asked how online news stories about the Aurora Theater Shooting frame serious mental illness and mass shootings. A content analysis was conducted on four news websites, two local publications and two national publications. This was designed to detect geographical trends in reporting. Key findings were a lack of causal attribution to SMI or any other cause, which disagreed with former research that found SMI as a commonly-attributed cause to gun violence after mass shootings in news media coverage. Gun restriction policy was found to be more prevalent in national news than in local news suggesting differences in coverage by geographic location. SMI and gun restriction policy proposals did not appear together in stories often pointing to a split in individual- or societal-level responsibility. A final finding was a singular mental health professional source utilized in the 187-story sample suggesting a lack of mental health experts in crime reporting after a mass shooting. Further research could explore the crime beat reporters' source-gathering habits particularly when dealing with crime purveyed by people with SMI as well as a study assessing mental health professionals' views on being used as a source in crime news reporting.